Breaking the Chains of Paper: Pioneering Electronic Notary Protocol Storage as the Dawn of a New Era in National Notarial Law - Mannas, Yussy Adelina; Fendri, Azmi; Baroto, Wisnhu Agung (Journal of Indonesian Legal Studies, 2024)
The Notary Protocol is a collection of documents constituting state archives that must be preserved and maintained by notaries in accordance with statutory provisions. Currently, the storage of notary protocols as state archives is predominantly conducted through conventional means, relying on paper-based media and manual handling. This traditional approach is fraught with several challenges, including vulnerability to loss and damage over time, the need for extensive physical storage space due to the increasing volume of archives, inefficiencies in document retrieval, and ineffective distribution of documents across organizational units and personnel. These limitations underscore the weaknesses of conventional archive management. Law Number 43 of 2009 on Archives permits the creation and storage of archives in various forms, including electronic media, thereby providing a legal basis for digital archiving. However, the existing regulatory framework governing notarial practices, particularly the Law on Notary Positions, does not explicitly address the electronic storage of notary protocols. This regulatory gap necessitates an analysis of the legal certainty surrounding the electronic archiving of notary protocols. Transitioning to electronic storage aligns with the demands of the Fourth Industrial Revolution (Industry 4.0) and Society 5.0, which emphasize digitalization and technological integration. This study explores the feasibility and legal implications of adopting electronic storage for notary protocols, aiming to enhance efficiency, security, and accessibility in the management of state archives.